Social studies education research for sustainable democratic societies: Addressing persistent civic challenges. (2nd January 2023) - Levy, Brett L. M.; Busey, Christopher L.; Cuenca, Alexander; Evans, Ronald W.; Halvorsen, Anne-Lise; Ho, Li-Ching; Kahne, Joseph; Kissling, Mark T.; Lo, Jane C.; McAvoy, Paula; McGrew, Sarah
ABSTRACT: Social studies education and research can and must play a central role in sustaining democratic societies. As we commemorate the 50th anniversary of this vital journal that aims to strengthen social studies education, democratic societies face numerous serious challenges. Although today's circumstances are unique, many of our current challenges have existed (and will continue to exist) in some form throughout the history of democracy. In this article, scholars from various sub-fields of social studies education explore how research, scholarship, and practice in the field can address seven of these persistent civic challenges: ecological sustainability, media literacy, equity and inclusion, civic engagement, political pluralism, civic competency, and sociohistorical change. Essays on each of these topics analyze relevant prior research and offer suggestions for how future research and scholarship can explore how educators can help to address these persistent civic challenges, with the goal of supporting robust participatory democracy.